2013
DOI: 10.1002/uog.12520
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of uterine vein thrombosis on transvaginal ultrasound

Abstract: Deep venous thrombosis (DVT) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…This is similar to the issues encountered with the imaging of vaginal mesh and slings, which are easily detected on ultrasound but not visible on x‐ray, MRI, or CT 38 . The only two previous studies evaluating the use of TVS for UVPT have concluded that ultrasound diagnosis is possible as it allows the transducer to be placed in close proximity to the pelvic veins, which facilitates a detailed examination of their morphology and blood flow 6,7 …”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…This is similar to the issues encountered with the imaging of vaginal mesh and slings, which are easily detected on ultrasound but not visible on x‐ray, MRI, or CT 38 . The only two previous studies evaluating the use of TVS for UVPT have concluded that ultrasound diagnosis is possible as it allows the transducer to be placed in close proximity to the pelvic veins, which facilitates a detailed examination of their morphology and blood flow 6,7 …”
Section: Discussionmentioning
confidence: 72%
“…The presence of any uterine, ovarian, tubal, or adnexal pathology was recorded. The uterine vessels were identified in the transverse plane as hypoechoic tubular structures originating at the level of the uterine internal os and traced laterally in the base of the broad ligament up to the iliac vessels 7 . In accordance with our standard practice, we used color Doppler to facilitate differentiation between uterine arteries and veins, and other similar tubular structures such as ureters or dilated Fallopian tubes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Once the pelvic organs had been examined, the UtV trunks were identified in the transverse plane as hypoechoic tubular structures originating at the level of the internal os. They were traced laterally at the base of the broad ligament up to the iliac vessels 5 . Application of color Doppler assisted the differentiation between uterine arteries and UtVs and other similar tubular structures, such as ureters or dilated Fallopian tubes.…”
Section: Methodsmentioning
confidence: 99%